PERSEPSI MAHASISWA INSTITUT AGAMA ISLAM NEGERI (IAIN) BONE MENGENAI BERITA HOAX TERKAIT VAKSIN SELAMA MASA PANDEMIK YANG TERSEBAR MELALUI MEDIA SOSIAL WHATSAPP (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2022)
The purpose of this research is (1) to find out how the perceptions of Islamic Family Law Students at IAIN Bone regarding vaccine hoax news during the pandemic that circulated on WhatsApp social media, and (2) to find out what actions were taken to reduce the circulation of this hoax news circulating. via social media WhatsApp. This type of research is qualitative descriptive research. The scientific approach in this research is to use a communication science approach, especially in mass communication. Data collection methods used are in-depth interviews, observation, and documentation. The sources of data for researchers came from theoretical books. Furthermore, data processing techniques and data analysis were carried out to answer the existing questions. The data analysis includes data reduction, data presentation, and drawing conclusions. The results of this study show that (1) how are the perceptions of students majoring in Islamic family law (HKI) IAIN Bone related to Hoax news about vaccines which are widely circulated on social media, especially WhatsApp social media which says that vaccines contain something that is not good for health. body. (2) how are the responses and actions taken by the students of the Islamic Family Law Department (HKI) IAIN Bone in responding to the circulation of this hoax news? Because where Hoax news is very disturbing and has a lot of negative impacts, especially on the general public.